Multi-Site Transfer Function Approach for Real-Time Modeling of the Ground Electric Field Induced by Laterally-Nonuniform Ionospheric Source - Kruglyakov, Mikhail; id_orcid:0 000-0002-6709-692X; Marshalko, Elena; Kuvshinov, Alexey; Smirnov, Maxim; Viljanen, Ari (Wiley-Blackwell, 2023)
We propose a novel approach to model the ground electric field (GEF) induced by laterally-nonuniform ionospheric sources in real time. The approach exploits the multi-site transfer function concept, continuous magnetic field measurements at multiple sites in the region of interest, and spatial modes describing the ionospheric source. We compared the modeled GEFs with those measured at two locations in Fennoscandia and observed good agreement between modeled and measured GEF. Besides, we compared GEF-based geomagnetically induced current (GIC) with that measured at the Mäntsälä natural gas pipeline recording point and again observed remarkable agreement between modeled and measured GIC. ISSN:1542-7390